Celebrating Halloween At Special Spot - Watkins, Howard::::::::: (1982)
Art Wille as Spiderman, Devon Bleile-Kratzer as Strawberry Shortcake, Adam Watkins as Count Dracula about to go out trick-or-treating Face masks on